2017
DOI: 10.15171/jcvtr.2017.24
|View full text |Cite
|
Sign up to set email alerts
|

Association of birth weight with abdominal obesity and weight disorders in children and adolescents: the weight disorder survey of the CASPIAN-IV Study

Abstract: Introduction: This study aims to evaluate the association of birth weight (BW) with weight disorders in a national sample of Iranian pediatric population. Methods: This nationwide survey was conducted among 25000 student’s aged 6-18 year-old students, who were selected using multistage cluster random sampling from 30 provinces of Iran in 2011-2012. Anthropometric measures were measured under standard protocols by using calibrated instruments. Abdominal obesity was defined based on waist circumference (WC) ≥90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. already reported similar results 36,37) . The interesting positive association between high parental education and abdominal obesity is worth noting.…”
Section: Discussionsupporting
confidence: 76%
“…The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. already reported similar results 36,37) . The interesting positive association between high parental education and abdominal obesity is worth noting.…”
Section: Discussionsupporting
confidence: 76%
“…Several previous studies have found significant associations between birth weight and abdominal obesity. Ansari [ 18 ] reported that high birth weight (> 4000 g) was associated with increased risk of abdominal obesity in children aged 6–18 years. Tian [ 19 ] and his colleague also found high birth weight (≥3500 g) to be a risk factor of abdominal obesity in people at 15–74 years old.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study in 7 to 8 year-old Japanese children [ 24 ] has demonstrated a higher WHtR in girls with birth weight < 3000 g, but not in boys. Rodríguez Vargas N [ 22 ] found that high birth weight was not a predictive factor for abdominal obesity in 7–11 years old children, while another study found high birth weight to be a risk factor of abdominal obesity in 6 to 18 year-old children [ 18 ]. In summary, there was still a considerable lack of research regarding the effect of birth weight on the risk of childhood abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Anthropometric data including height and weight were measured according to a standard program using calibrated devices by a trained staff of health-care systems. The BMI was calculated by dividing the weight in kilograms by the square of the height in meters [42,43]. Overweight and Obesity status was determined based on BMI z-scores that were calculated by using World Health Organization gender-specific BMI-for-age growth charts [18].…”
Section: Bmimentioning
confidence: 99%